SYSTEM AND METHOD FOR PRIORITIZING AND BALANCING SIMULTANEOUS AUDIO OUTPUTS IN A HANDHELD DEVICE (2007)
A system and method for prioritizing multiple audio sources and balancing them in a single combined output in a handheld device. Audio sources are sensed and combined with the level of each source subject to adjustment by an attenuator/amplifier. A priority logic unit controls the attenuator/amplifier associated with each source. the level of each source being combined is adjusted on the basis of the character of the sources being combined and a set of programmed rules. For example, if source A is a high priority source (e.g. a telephone ring or other alert tone) and source B is a lower priority source (e.g. a music program) then the sound management system may lower the volume on source B combine with source A and output the result. Alternatively, source A may be raised in volume, combined with source B, and then output. In one embodiment, the sound management system is integrated with a palm sized handheld computer system.